Spinal lesions: a comprehensive radiologic overview - Alam, Zahin; Syed, Mohammed Usman; Siddiqui, Tausif Ahmed; Gunturi, Aditya; Reddy, Brij; Alam, Zarah; Rahman, Akm A. (Frontiers in Radiology, 2025)
Spinal lesions encompass a diverse range of pathologies, including primary and secondary tumors, infectious processes, vascular malformations, traumatic injuries, and degenerative conditions, each with distinct imaging characteristics crucial for accurate diagnosis and management. Imaging plays vital roles in assessing lesion morphology, anatomical localization, and neurological impact, guiding clinical decision-making and therapeutic planning. This review systematically explores spinal lesions based on their anatomical compartments, highlighting key radiological features and providing a comprehensive reference for radiologists.